Weekly fluctuations in subjective and objective measures of internal training load and their relationships in male elite rowers - Dai, X.; Yan, J.; Bi, X. (Journal of Sports Science & Medicine, 2025)
Subjective and objective methods are commonly used to evaluate the load and physiological adaptations of athletes in training. However, there is a lack of data and their relationship concerning these tools in professional rowing training. This study aimed to investigate the relationship between the subjective and objective training loads of male rowers during a mesocycle. Field data were collected from 26 professional rowers over 6 consecutive weeks. Subjective training load variables (perceived exertion, acute: chronic workload ratio, training monotony and strain), and objective variables (white blood cell, red blood cell, blood urea, creatine kinase, testosterone, and cortisol) was collected, and correlations between various TL`s were analyzed. All participants completed 6 weeks of training, which consisted of resistance (315 ± 88.5min/week), on-water (817.5 ± 9min/week), ergometer (341.9 ± 194.1min/week) and functional training (60min/week). Week 5 had the highest average weekly subjective training load (10849.23 ± 1361.14 AU), whereas Week 2 showed the highest training monotony (TM) with statistically significant differences compared to Week 1, week 3, week 5 and week 6 (p < 0.05), with small to moderate effect sizes (ES: 0.275-0.619). There were correlations among all the subjective training load variables. A positive correlation was found between sRPETL and TS (r = 0.80). Blood urea (BU) was positively correlated with weekly sRPETL (r = 0.44, p < 0.05), TM (r = 0.40, p < 0.05), TS (r = 0.43, p < 0.05) and ACWR (r = 0.44, p < 0.05). Similarly, creatine kinase (CK) was also associated with these indicators (r = 0.50-0.60). Testosterone and cortisol showed a consistently negative correlation (r = -0.64), but no relationship were found between these hormones and subjective training load. In conclusion, this study demonstrates a significant correlation between subjective and objective training loads in elite rowers. Our findings provide empirical evidence that ACWR, TM and TS serve as sensitive indicators of biochemical markers (CK and BU) fluctuations in professional rowing athletes. Given the correlation between the above objective and subjective indicators, coaches can adjust the training schedules based on the subjective data during training week, and combine with hematological tests to further promote positive adaptations.